Optimalisasi Investasi Dana Haji Melalui Sukuk dan Deposito Bank Syariah Terhadap Pengembangan Dana Haji Di Indonesia Periode 2016 - 2019 - Safitriawati, Tita; Fauziah Ulfah, Indar; Widayati, Neneng (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
Abstract: Development of Hajj funds in Indonesia for the 2016-2019 period. This research uses a descriptive method by analyzing data taken from secondary data directly to the BPKH website and literature study. The data analysis technique used is data collection, data reduction, data display, verification, and concluding. The results of this study indicate that the optimization of investment in hajj funds through Sukuk and Islamic bank deposits has increased from year to year so that it can increase financing in organizing Hajj. In 2018, referring to PP. 5 In 2018, BPKH plans to differentiate Hajj fund investments in gold (5%), direct investment (15%), and other investments (10%). Besides, the proportion of placement of funds in savings/time deposits decreased to 50% and placements in Sukuk to 20%. Then, in 2020, the proportion of placement of funds in savings/time deposits will again decrease to only 30% and transfer this proportion to Sukuk and direct investment.